Charge transfer during sodium-ion intercalation in graphite-like anodes as determined by Raman spectroscopy - Pascal Puech; Damien Tristant; Shaorui Chen; Shae Wetzel; Yuxin Xiang; Tianzhao Hu; Lili Zhang; Marc Monthioux; Feng Li (Carbon Trends)
Sodium intercalation in graphite is known to be unstable, posing a challenge for energy storage applications based on this cation. This study combines Raman spectroscopy with first-principles calculations, including electron-phonon coupling, to investigate charge transfer mechanisms and stability in Na-intercalated graphite. Contrary to theoretical predictions on a pure Na graphite intercalated compound, Raman data show no evidence of so-called mechanical coupling between Na+ ions and graphene layers. As we have selected a partially graphitized carbon with an intense 2D band for the anode, analyzing the Raman shifts of both the G and 2D bands is possible and allows us to discriminate between doping and lattice expansion treated as strain effects. The observed shifts are fully explained by a simple charge-transfer mechanism to each graphene layer. At stage one intercalation, a charge transfer value of -0.17±0.02 |e-| per carbon atom is determined. These findings highlight the ability of Raman spectroscopy to quantify charge transfer and differentiate intercalation behaviors between the various alkali metals.